2020
DOI: 10.1177/1040638720981019
|View full text |Cite
|
Sign up to set email alerts
|

Randomly primed, strand-switching, MinION-based sequencing for the detection and characterization of cultured RNA viruses

Abstract: RNA viruses rapidly mutate, which can result in increased virulence, increased escape from vaccine protection, and false-negative detection results. Targeted detection methods have a limited ability to detect unknown viruses and often provide insufficient data to detect coinfections or identify antigenic variants. Random, deep sequencing is a method that can more fully detect and characterize RNA viruses and is often coupled with molecular techniques or culture methods for viral enrichment. We tested viral cul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…We emphasize the importance of providing novel sequence data in accordance with recent studies, in which the complete genomic sequence data of CDV are increasingly reported. This will greatly facilitate a better understanding of both the evolution of CDV and epizootic patterns in the near future [ 47 , 64 , 65 , 66 , 67 ]. In our study, we used a recently published pan-genotype CDV-specific amplicon-based sequencing method developed for the Oxford Nanopore Technologies platform [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…We emphasize the importance of providing novel sequence data in accordance with recent studies, in which the complete genomic sequence data of CDV are increasingly reported. This will greatly facilitate a better understanding of both the evolution of CDV and epizootic patterns in the near future [ 47 , 64 , 65 , 66 , 67 ]. In our study, we used a recently published pan-genotype CDV-specific amplicon-based sequencing method developed for the Oxford Nanopore Technologies platform [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Next generation sequencing (NGS) technologies are increasingly being used to detect and characterize pathogens in wildlife [ 41 – 44 ]. MinION (Oxford Nanopore Technologies, Oxford, UK) has been used in many areas of virology, for instance, metagenomics or sequencing of complete genomes [ 45 48 ]. Amplicon-based NGS sequencing of specific pathogens is a method for rapid detection and genomic characterization of target pathogens which may yield high-coverage genomic sequence information [ 12 , 49 – 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate sequencing at the beginning and end of the genome in the noncoding region was consistent when sequencing other RNA viruses, such as Zika, using the tiling primer approach [ 29 ]. Newer, randomly primed, strand-switching amplification protocols have been recently developed that may complement tiling primer-based sequencing, with particular strength in the agnostic sequencing of divergent RNA viruses [ 50 ]. However, this protocol was not available at the time of sequencing in Ukraine, and remain to be robustly tested in low-resourced laboratories or field settings.…”
Section: Discussionmentioning
confidence: 99%